The Effect Of Corporate Advertising And Social Campaigns On Consumer Perceptions: A Case Study Of Coca-Cola's 'Together Tastes Better' Campaign In Indonesia During The Covid-19 Pandemic - Muhammad Rozan Fikri; Vivi Silvia Huri; Lilis Satriah; Imron Rosyidi; Mohammad Afid Syafiri (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − This study aims to analyze the influence of corporate advertising, especially in the form of social campaigns, on consumer perception of the Coca-Cola brand during the COVID-19 pandemic in Indonesia. The main issue examined was how the